Development innovation: Fad, silo or catalyst? - and Ramalingam, Ben (2015)
In the first of a two-part blog piece, Ben Ramalingam, affiliate of the Overseas Development Institute / Institute of Development Studies, discusses the challenges of implementing innovation in to the development sector - from keeping expectations realistic to managing the innovation process and assessing impact and value.